THE EFFECT OF MARKETING MIX UPON THE CONSUMER’S DECISION MAKING TO BUY A PRODUCT AT PT GRIYA PAGELARAN BOGOR - Sumardjono Sumardjono; Heni Ardila (The Management Journal of Binaniaga, 2018)
The purpose of this study is to determine and prove whether the variables of  the marketing mix significantly has influenced  the consumer’s decision making to buy the product at PT. Griya Pagelaran Bogor. The population of this study are the number of unknown sampling determination using Maximum Likelihood estimation method by taking samples of consumers who their needs has met with the researcher requirement as many as 150 respondents. The analytical method has used is Structural Equation Modeling (SEM) using AMOS 21 program. The result of the research shows that 1) Product Variables have a significance level of 0.05 which is 1,965 > 1,96 and value (p) probability 0,49 ≤ 0.05. Then Ha is accepted and significant effect. 2) Variable Price level of significance 0.05 is 2.023 > 1.96 and has a probability of 0.43 which is below 0.05. And the value (p) probability ≤ 0.05 then Ha is accepted and significant effect. 3) Place Variables significance level of 0.05 is 2.251 > 1.96 and has a probability of 0.24 which  is below 0.05. And the value (p) probability ≤ 0.05 then Ha is accepted and significant effect. 4) Promotion Variables 0.05 level of significance is 3.435 > 1.96 and has a probability in accordance with the recommended. And the value (p) probability ≤ 0.05 then Ha accepted and significant effect.Keywords: Marketing Mix, Consumer Purchase Decision, SEM